MUSEUM GARIS WAKTU TERUMBU KARANG - Carolina Tedjapranata (Jurusan Arsitektur dan Perencanaan, 2021)
Climate change causes global warming on earth. This event was preceded by the start of the Industrial Revolution, a shift in the production system from human power to machine power, which encouraged the construction of factories and the transportation system to support manufactured goods. This thing increases the carbon emission gas in the air. Coastal areas are the regions generally defenseless against the adverse consequences of climate change. Coral reefs are oceanic environments that are influenced by environmental change. The condition of coral reefs is getting worse along with the earth's rising temperature and can cause death. This cause affects not only humans but also marine life. Gili Matra is a diving and snorkeling tourism destination that is rich in coral reefs. Supported by the development of a coral garden by the government in Gili Meno fits perfectly with the purpose of this project. By using experimental methods and the technology to build the